Benefit in Kind: Should It Be Exempted from Zakat? - Hamat, Zahri; Firdaus, Radin Badaruddin Radin; Shaharudin, Samsurijan Mohamad (Universiti Sains Islam Malaysia (USIM), 2017)
In general, emoluments, allowances and all forms of income related to employment are considered as employment income zakat in Malaysia. However, based on the practice of zakat institutions in Malaysia, not all that is received in relation to employment is liable for mandatory zakat, including all forms of benefit in kind (BIK). On the other hand, in terms of taxation practice, all benefits in kind received by an employee are taxable by Inland Revenue Board of Malaysia (LHDN), except for benefits listed in Paragraph 9. BIK refers to benefits given to employees, which cannot be convertible into money, such as motorcar and household furnishings, apparatus and appliances. It is worth noting that the discussion on the imposition of zakat on benefits in kind has not been given enough thought and justifiably raises questions. Therefore, in this study, three central questions have been raised with regards to BIK and zakat in Malaysia. Should BIK be considered under the category of “whatever received related to employment”? Why BIK should be subjected to employment income zakat? How BIK can be charged under the context of employment zakat? Based on the content analysis method, this paper presented a brief review to answer these questions. In general, this study is of the opinion that BIK is zakatable and LHDN’s income tax assessment method could be adopted for employment income zakat accounting.